The historical-cultural theory as a basis in the constitution of the universal design for learning - Sebastián-Heredero, Eladio (2023)
Universal Design for Learning (UDL) was conceived as a form of curricular reorganization, specifically called differentiation, with the goal of eliminating barriers to learning for all students. It was created with an inclusive perspective where everyone, including people with disabilities, can fully develop their skills and abilities based on three principles: propose changes in the way of motivating and involving students; present the contents and activities in a different way and organize the evaluation of the students in different ways that allow, according to their intelligence, to be able to present what they have learned in a clearer way for them. According to this, in this article in the form of an essay, we intend to discuss the relationship that exists between DUA and the concept of Vygotskyan learning and Vygotsky's historical-cultural theory. To do this, we start from the understanding that this curricular perspective presents the possibility of generating curricula that contribute to the development of all students, disabled or not. This personal development and learning occur, according to the DUA, from relationships in the school context and in the environment, in that subjective and social space of encounter and exchange, which allows them to learn and develop their abilities to the maximum. A concrete form of construction of learning is evident, since it stands out in its guidelines or guidelines, that the curriculum is not a barrier to the construction of their thinking and acting in society, connected with Vygotsky's assumptions, focusing on the elaboration of objects, tools and processes from their zone of proximal development.